Comparison Between Laparoscopic and Robotic Surgery in Elderly Patients With Endometrial Cancer: A Retrospective Multicentric Study - Corrado, Giacomo; Vizza, Enrico; Perrone, Anna Myriam; Mereu, Liliana; Cela, Vito; Legge, Francesco; Hilaris, Georgios; Pasciuto, Tina; D’Indinosante, Marco; La Fera, Eleonora; Certelli, Camilla; Bruno, Valentina; et al. (Frontiers in Oncology, 2021)
Introduction: Studies in which different types of minimally invasive approaches in elderly patients are compared are missing. The aim of this study was to evaluate the surgical and oncological outcomes of patients of 70 years or older who had undergone laparoscopic (LS) or robotic surgery (RS) for endometrial cancer (EC). Materials and methods: This is a retrospective multi-institutional study in which all the patients who had undergone minimally invasive surgery for EC were considered. The inclusion criteria were: EC confirmed at definitive histological examination, FIGO stage I-IV and age of 70 years or older. Owing to the non-randomized nature of the study design and the possible allocation biases arising from the retrospective comparison between LPS and RS groups, we also performed a propensity score-matched analysis (PSMA). Results: A total of 537 patients with EC were included in the study: 346 who underwent LS and 191 who underwent RS. No significant statistical differences were found between the two groups in terms of surgical and survival outcomes. 188 were analyzed after PSMA (94 patients in the LS group were matched with 94 patients in the RS group). The median estimated blood loss was higher in the LS group (p=0.001) and the median operative time was higher in the RS group (p=0.0003). Conclusions: Our study showed that when compared LS and RS, none of the two approaches demonstrated to be superior in surgical and survival outcomes. For this reason, each patient should be evaluated individually to determine the best surgical approach.